A dynamic species distribution model of Glossina subgenus Morsitans: The identification of tsetse reservoirs and refugia - Visser, Mark H. de; Messina, Joseph P.; Moore, Nathan J.; Lusch, David P.; Maitima, Joseph (Wiley, 2010)
Tsetse flies are the primary vector for African trypanosomiasis, a neglected tropical disease that affects both humans and livestock across the continent of Africa. In 1973 tsetse were estimated to inhabit 22% of Kenya; by 1996 that number had risen to roughly 34%. Efforts to control the disease are hampered by a lack of information and costs associated with the identification of infested areas. To aid control efforts we have constructed the Tsetse Ecological Distribution Model (TED Model). The TED Model is a raster based dynamic species distribution model that predicts tsetse distributions at 250 m spatial resolution, based on habitat suitability and fly movement rates, at 16‐day intervals. Although the TED Model can be parameterized to any tsetse subgenus/species requirements, for the purpose of this study the TED Model was parameterized to identify suitable habitat for Glossina subgenus Morsitans. Using the TED Model we have identified where and when Glossina subgenus Morsitans populations should be constrained by unfavorable ecological conditions to particular parcels of suitable habitat. It is our hope that by utilizing the predicted locations of tsetse reservoirs and refugia, control efforts will be better able to target tsetse populations when they are spatially constrained, thus maximizing limited available resources.